Nuremberg [videorecording (DVD)] - Tyler, Brian (Composer) (Sony Pictures Home Entertainment, 2026)
"The Allies, led by the unyielding chief prosecutor, Robert H. Jackson, have the task of ensuring high-ranking Nazi officials answer for the Holocaust in the trial of the century while a US Army psychiatrist is locked in a dramatic psychological duel with former Reichsmarschall Hermann Göring, revealing the sobering truth that ordinary men commit extraordinary evil." --